2004
DOI: 10.1111/j.1075-122x.2004.21328.x
|View full text |Cite
|
Sign up to set email alerts
|

Occult Metastases in Axillary Lymph Nodes as a Predictor of Survival in Node-Negative Breast Carcinoma with Long-term Follow-up

Abstract: Increased detection rate in the lymph nodes is seen with serial sectioning or immunohistochemistry (IHC), but the importance of occult metastases is not resolved. IHC is still not recommended in routine examination of lymph nodes. Axillary lymph nodes from 385 node-negative breast cancer patients with a median follow-up of 25 years were examined with IHC for cytokeratins, applied on routine sections. The association between classic histopathologic prognostic factors and the presence of occult metastases was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 22 publications
1
52
0
1
Order By: Relevance
“…Furthermore, in patients who did not receive adjuvant systemic therapy, the prognosis of a single MM was comparable to a single macrometastasis [30]. Negative prognostic impact has also been reported by Reed et al [31]. In their study of 385 women with BC, poorer prognosis was found in those 45 cases with occult metastases compared to their truly node negative counterparts.…”
Section: Analysis Of the Sentinel Lymph Nodementioning
confidence: 63%
“…Furthermore, in patients who did not receive adjuvant systemic therapy, the prognosis of a single MM was comparable to a single macrometastasis [30]. Negative prognostic impact has also been reported by Reed et al [31]. In their study of 385 women with BC, poorer prognosis was found in those 45 cases with occult metastases compared to their truly node negative counterparts.…”
Section: Analysis Of the Sentinel Lymph Nodementioning
confidence: 63%
“…Axillary lymph node involvement has been recognized as the most important prognostic factor in breast cancer, despite the fact that many other parameters have been evaluated in recent years (O'Hanlon et al 2002;Reed et al 2004). Recently, Reed et al (2004) demonstrated that metastases larger than 2 mm predicted poorer relapse-free survival rate and that subcapsular location of metastases was a strong predictor of overall survival in their sample.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of the true false-negative rates for the detection of metastases range from 5 to 15%. 36,37 Analysis of the seven molecular markers tested demonstrated that the majority of mammaglobin/CK19 molecular false positives were also positive with several other breast tumor markers not expressed in the vast majority of H&E-negative samples. Samples demonstrat- ing significant expression of mammaglobin and/or CK19 have a high probability of also expressing the other markers tested, including B305D, GABA, B726, and PDEF, markers previously demonstrated to have increased expression in cancerous breast tissues.…”
Section: Discussionmentioning
confidence: 99%